Ecological Dynamics Impacting Bluetongue Virus Transmission in North America - Mayo, Christie; McDermott, Emily; Kopanke, Jennifer; Stenglein, Mark; Lee, Justin; Mathiason, Candace; Carpenter, Molly; Reed, Kirsten; Perkins, T. Alex (Frontiers in Veterinary Science, 2020)
Bluetongue virus (BTV) is an economically important arbovirus that is transmitted to domestic and wild ruminants by certain species of hematophagous Culicoides midges. The disease resulting from infection with BTV can impact international trade and movement of livestock, the economics of livestock production, and animal welfare. Recent changes in the epidemiology of Culicoides-transmitted viruses, particularly the emergence of exotic BTV genotypes in Europe, have highlighted the devastating economic consequences of BTV epizootics and the dynamic nature of transmission across host-vector landscapes. Incursion of novel serotypes of BTV into historically enzootic countries or regions, including the southeastern United States (US), Israel, Australia, and South America, have also occurred, reflecting diverse means for spread of these viruses. The abundance of BTV strains and multiple reassortant viruses circulating in Europe and the US in recent years demonstrates considerable genetic diversity of BTV strains and implies a history of reassortment events within the respective regions. While a great deal of emphasis is rightly placed on understanding the epidemiology and emergence of BTV beyond its natural ecosystem, the ecological contexts in which BTV maintains an enzootic cycle may also be of great significance. This review focuses on describing our current understanding of ecological factors driving bluetongue virus transmission in North America. Information presented in this review can help inform future studies that may elucidate factors that are relevant to longstanding and emerging challenges associated with prevention of this disease.